The Implementation of Multicultural Based Learning in Reducing Intolerance Attitudes among Students - Hadiwijaya, Munawwir; Adi, Adi (Universitas Muhammadiyah Gresik, 2018)
The purpose of this study is to determine the effectiveness of multicultural based learning with Multiple Perspectives Approach in suppressing intolerance among students. The result shows that there is a significant influence of multicultural learning models with multiple perspective approaches to students’ tolerance levels: 4.56 (control) and 6.28 (experimental). The tolerance level of students after applying multicultural based learning methods with multiple perspective approaches is better (X_A1n = 6.76) compared to the tolerance level of students using conventional learning methods (X_A2 = 4.11). The students’ four values emphasized on the implementation of multicultural based learning methods are increased.